International chemical agents Conference, 3-5 April 2002, Hillerød, Denmark [CD-ROM incl.] (Dansk Toksikologi Center, 2002)
"The conference will bring together legislators and decision-makers, suppliers and users of chemicals, companies developing and providing tools for the communication, assessment or management of chemical hazards and risks, social partners representing employers or employees and their organisations, representatives from the chemical industry as well as health and safety experts specialized in the field of chemicals at work. The conference will be a forum for identifying the state-of-the-art in the field of safe use of chemicals at work with focus on the European situation and it will bring together people from across Europe as well as from other parts of the world with interest in Europe. The objective of the conference is to focus on requirements, expectations and actions necessary for workplace risk assessment. This involves providing and obtaining information about chemical agents and the processing and transfer of this information into an efficient protection of workers handling chemicals at the workplace and of the environment."